2018
DOI: 10.1128/msphere.00482-17
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Voltage-Dependent Anion Channel Protein Por1 Positively Regulates the Nuclear Localization of Saccharomyces cerevisiae AMP-Activated Protein Kinase

Abstract: AMP-activated protein kinases (AMPKs) sense energy limitation and regulate transcription and metabolism in eukaryotes from yeast to humans. In mammals, AMPK responds to increased AMP-to-ATP or ADP-to-ATP ratios and is implicated in diabetes, heart disease, and cancer. Mitochondria produce ATP and are generally thought to downregulate AMPK. Indeed, some antidiabetic drugs activate AMPK by affecting mitochondrial respiration. ATP release from mitochondria is mediated by evolutionarily conserved proteins known as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…5D). These results are consistent with a growing number of papers that have shown that a sub-population of the Snf1-Gal3 isoform is present in the nucleus under normal conditions 52 60 70 , as well as enriched in the nucleus upon glucose starvation 34 35 36 . In addition, Sak1 is needed for Snf1 nuclear localization 71 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…5D). These results are consistent with a growing number of papers that have shown that a sub-population of the Snf1-Gal3 isoform is present in the nucleus under normal conditions 52 60 70 , as well as enriched in the nucleus upon glucose starvation 34 35 36 . In addition, Sak1 is needed for Snf1 nuclear localization 71 .…”
Section: Discussionsupporting
confidence: 92%
“…Further studies need to be executed to address if Sip1 or Sip2 can translocate into the nucleus in the absence of Gal83. Intriguingly, just recently the Mitochondrial Voltage-Dependent Anion Channel Protein Por1 (yVDAC1) has been shown to enhance Snf1 nuclear enrichment by promoting the nuclear enrichment of Gal83 70 . This unexpected finding serves to emphasize that there is still much to learn about the role Snf1 kinase plays in response to changing environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In S. cerevisiae, Gal83 phosphorylation sites have been identified in high-throughput studies [95], but the effect of such modifications is not known. Some evidence suggests a role for the mitochondrial voltage-dependent anion channel (VDAC) protein, Por1, promoting Gal83 nuclear localization by a mechanism that is distinct from Snf1 activation during growth in glycerol/ethanol [96], and for the nuclear export receptor, Crm1, in the nuclear exclusion of Gal83 during growth on abundant glucose [97]. P. pastoris OXPHOS mutants share phenotypes of DScpor1 mutant, such as normal Snf1 activation by glucose derepression and the absence of induction of genes regulated by SNF1 signaling [96].…”
Section: Feedback Loop Between Peroxisomes and Mitochondria Senses Cellular Metabolic Statusmentioning
confidence: 99%
“…Some evidence suggests a role for the mitochondrial voltage-dependent anion channel (VDAC) protein, Por1, promoting Gal83 nuclear localization by a mechanism that is distinct from Snf1 activation during growth in glycerol/ethanol [96], and for the nuclear export receptor, Crm1, in the nuclear exclusion of Gal83 during growth on abundant glucose [97]. P. pastoris OXPHOS mutants share phenotypes of DScpor1 mutant, such as normal Snf1 activation by glucose derepression and the absence of induction of genes regulated by SNF1 signaling [96]. However, the deletion of the only POR1 homolog, or overexpression of Por1 in P. pastoris, did not produce the same phenotypes observed in the OXPHOS mutants and Gal83 localization was unaffected by Por1.…”
Section: Feedback Loop Between Peroxisomes and Mitochondria Senses Cellular Metabolic Statusmentioning
confidence: 99%
“…Recently, AMPK-related protein kinase-5 (ARK5), a crucial member of the human AMP-activated protein kinases (AMPKs) family, has been identified to be associated with metastasis of cancer cells (4). Metastasis is a complex multistep process involving cell migration and invasion.…”
Section: Introductionmentioning
confidence: 99%